Assessment of Knowledge and Practices about Menstrual Health among Adolescent Girls of an Urban Slum in Mumbai. - Prateek Saurabh Shrivastava,; Saurabh RamBihariLal Shrivastava, (Universiti Kebangsaan Malaysia, 2013)
Adolescence is a critical period of life marked by biological, social and psychological changes for an individual.